Evidence of Pneumopericardium after Elective Ovariectomy in a Peritoneopericardial Diaphragmatic Hernia-Affected Dog: A Case Report - Debora Campanile; Mariateresa Cafaro; Serena Paci; Michele Panarese; Giammarino Sparapano; Marina Masi; Antonio De Simone (Animals, 2024)
Peritoneopericardial diaphragmatic hernia (PPDH) is an opening between the pericardial sac and the pleuroperitoneal membrane. Pneumopericardium is an infrequent complication of PPDH. This condition is a serious circumstance in which free gas accumulates in the pericardial sac. The present report describes the occurrence of pneumopericardium and pericardial effusion after elective ovariectomy in a dog affected by PPDH. The presence of an umbilical and diaphragmatic hernia was highlighted during ovariectomy, and a pneumopericardium was seen during an X-ray exam. At the time of admission to the hospital, the dog was asymptomatic. The diagnosis was performed by X-ray and ultrasonographic exams. Computed tomography examination confirmed the diagnosis and directed for a surgical approach of the congenital defect. Surgery resulted in resolution of PPDH and of pneumopericardium.